Review on Trypanosoma cruzi: Host Cell Interaction - Wanderley de Souza; Tecia Maria Ulisses de Carvalho; Emile Santos Barrias (International Journal of Cell Biology)
Trypanosoma cruzi, the causative agent of Chagas' disease, which affects a large number of individuals in Central and South America, is transmitted to vertebrate hosts by blood-sucking insects. This protozoan is an obligate intracellular parasite. The infective forms of the parasite are metacyclic and bloodstream trypomastigote and amastigote. Metacyclic trypomastigotes are released with the feces of the insect while amastigotes and bloodstream trypomastigotes are released from the infected host cells of the vertebrate host after a complex intracellular life cycle. The recognition between parasite and mammalian host cell involves numerous molecules present in both cell types. Here, we present a brief review of the interaction between Trypanosoma cruzi and its host cells, mainly emphasizing the mechanisms and molecules that participate in the T. cruzi invasion process of the mammalian cells.